ERRORS IN NARRATIVE TEXT COMMITTED BY STUDENTS OF GRADE XI OF VOCATIONAL HIGH SCHOOL STATE 4 SURAKARTA ACADEMIC YEAR 2014/2015 - Mulyono, Eko (Jurnal Penelitian Humaniora, 2017)
This study aimes to identify the types of errors in the students writing, to know the frequencies of each type of errors, and to investigate the causes of errors. There are three types of errors occured in the students writing namely lexical error, syntactical error, and discourse error. The errors can be categorized into twenty four subcategories of errors: wrong spelling words (10,35%), wrong selection words (15,53%), omission verb (0,74%), omission v-ing after preposition for (0,55%), addition unnecessary verb (0,74%), using simple present tense refers to simple past (22,37%), use simple future instead of past future (2,40%), using irregular past verb tense after to infinitive (2,40%), addition final ed after to infinitive (1,85%), addition v-ing after to infinitive (1,11%), addition double marking verb (1,66%), omission to be (11,65%), addition to be (1,29%), omission s/es in the use of plural noun (2,40%), addition s in singular noun (1,29%), omission article (6,47%), addition unnecessary article (1,66%), wrong article (1,11%), wrong subject pronoun (2,03%), wrong object pronoun (0,55%), wrong possessive pronoun (2,03%), generic structure (2,96%), reference (2,03%), wrong selection conjunction (4,81%). The most dominant error is in syntactical error i.e. using simple present tense refers to simple past with the percentage 22,37%. Those errors are caused by four aspects, they are overgeneralization, incomplete application of rules, ignorance of rule restrictions, and false concept hypothesized.